(3GdeYQH GdeHjf YeG JVefg GdCfjS GdeWQH hQhVI GdfSQjfs - (3eMeO Hf bGSe Hf eMeO Hf YHO GdhGMO GdaGSj, CHh YHO Gddg, GHf RGchQ , J (B1120 (3g` s
(3ChdgG (B:s
(3hHYO , gPG JdNjU eYQH YeG ETJed Ydjg GdCfjS GdeWQH ai CNHGQ aGS hedhc GdeZQH , HjO Gfi PjdJg RjGOI ddJYjjf HeG GSJCKQJ Ydjg QhVI GdfSQjf ef edhc Hfi eQjf s
(3BNQgG (B:s
(3hdGMhd hdGbhI EdG HGddg GdYdi GdYXje hBNQ OYhGfG Cf GdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3ef U (B22 (3C (B- (3U(B52 (3Hs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
(3GNJUGQ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B145s
Keywords: (3GdJGQjNs